Diseño e implementación de un sistema de agricultura de precisión, para la optimización del agua de riego del Cantón Chambo. - Lara Aguayo, Wilson Alejandro (2021)
The subject of this study is: "Design and implementation of a precision agriculture system for the optimization of irrigation water in the Chambo canton". Through this issue, a problem that required attention has been identified, because an efficient control of humidity is needed in the crops, supplying the water required for each one and thus avoiding the waste of the liquid, being this as a response with a lower impact to the environment. To provide a solution, it was proposed to work with a wireless network of sensors that measure humidity in different parts of the field, with these it was possible to determine the amount of water required and by using electro-valves to control the intake of water to the crops, likewise, the cessation of supply considering the dimensions of the land and the distances of each crop. The synthetic and analytical methods were used, the method of scientific observation. In addition, the experimental method was used since all the information provided by the study was collected, processed and analyzed. The system is made up by: sensors, solenoid valves, a SIM800L monitor, Arduino 1 microcontroller, Xbee coordinator, SIM800L, Arduino NANO, control board, LCD screen, DS3232, Xbee router. A solar panel, TP4056 lithium battery charger module and XCTU software were also incorporated. The results obtained when the system was implanted were: Compared with various products between the uncontrolled water flow using a base of 298,944 L, the following variants were obtained with a controlled water flow: with the pea he used 44,982 L obtaining an optimization of 85% water. Onion crops used 22.607 L an optimization of 92% of water. Head lettuce crops used 18,433 L with an optimization of 93.83% of water: The super chola potato 22,259 L with an optimization of 92.55%. Being the system effective in water consumption.